2017
DOI: 10.1039/c7nj01893b
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties of quinoxalin-2(1H)-ones: application in the preparation of an azide-based fluorogenic probe for the detection of hydrogen sulfide

Abstract: Fluorescent quinoxalinones with good quantum yields were obtained and used in the preparation of a probe for the detection of H2S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Moreover, while the reduced derivatives of quinoxalin‐2(1 H )‐ones at the carbonyl groups could show fluorogenic properties (Figure 1), [5] the photophysical properties of these derivatives have been relatively overlooked, [6] with only a limited number of studies focusing on their fluorogenic properties having been reported to date [2c,5] . This is somewhat surprising, as these derivatives have potential utility as fluorogenic probes for the detection of valuable bioactive substances [5] . For example, this photophysical property of the quinoxalin‐2(1 H )‐ones could be used in chemo‐sensing studies or to monitor biological reactions.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, while the reduced derivatives of quinoxalin‐2(1 H )‐ones at the carbonyl groups could show fluorogenic properties (Figure 1), [5] the photophysical properties of these derivatives have been relatively overlooked, [6] with only a limited number of studies focusing on their fluorogenic properties having been reported to date [2c,5] . This is somewhat surprising, as these derivatives have potential utility as fluorogenic probes for the detection of valuable bioactive substances [5] . For example, this photophysical property of the quinoxalin‐2(1 H )‐ones could be used in chemo‐sensing studies or to monitor biological reactions.…”
Section: Figurementioning
confidence: 99%
“…Yuan and Mao employed Cu 2 O and tert ‐butyl peroxybenzoate in the oxidative coupling of quinoxalin‐2(1 H )‐ones with alcohols to obtain the desired products [4] . Moreover, while the reduced derivatives of quinoxalin‐2(1 H )‐ones at the carbonyl groups could show fluorogenic properties (Figure 1), [5] the photophysical properties of these derivatives have been relatively overlooked, [6] with only a limited number of studies focusing on their fluorogenic properties having been reported to date [2c,5] . This is somewhat surprising, as these derivatives have potential utility as fluorogenic probes for the detection of valuable bioactive substances [5] .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Multicomponent reactions have become a hot field in modern organic chemistry in recent years because multicomponent reaction can form multiple chemical bonds in one step in comparison with the traditional synthesis method, thus realizing the simple, efficient, and atomic economic synthesis of structural diversity compounds. Quinoxalines and their derivatives are one of the important organic compounds because they have been widely applied in organic synthesis, material chemistry, agrochemical industries, and pharmaceutical chemistry (TenBrink et al, 1994 ; Monge et al, 1995 ; Badran et al, 2003 ; Refaat et al, 2004 ; Hoogewijs et al, 2013 ; Nakane et al, 2015 ; Renault et al, 2017 ). Although a plenty of two-component reactions for the synthesis of quinoxalinones were achieved (Hong et al, 2019 ; Jin et al, 2019 ; Ke et al, 2019 ; Liu et al, 2019 ; Wang et al, 2019 , 2020 ; Wei et al, 2019 ; Xie et al, 2019 ; Xue et al, 2019 ; Yan et al, 2019 ; Zhang H. et al, 2019 ; Zhang W. et al, 2019 ; Bao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%